ANALISIS KEMAMPUAN LITERASI DIGITAL SISWA SEKOLAH DASAR KELAS V - Gita Rahelia Br Bangun; Albertus Hartana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the increasing integration of digital technology in elementary school learning, which has not been fully balanced by students’ ability to evaluate information, understand digital ethics, and use technology responsibly. This study aims to analyze the digital literacy skills of fifth-grade elementary school students, identify the influencing factors, and describe teachers’ strategies in developing digital literacy in regular classroom learning. This research employed a qualitative approach using a case study method conducted at Kanisius Demangan Baru 1 Elementary School and Kentungan Public Elementary School in Yogyakarta. Data were collected through observation, semi-structured interviews, questionnaires, and documentation, and analyzed through data reduction, data display, and conclusion drawing using triangulation techniques to ensure credibility. The findings indicate that students’ digital literacy skills are at an early developmental stage. Students possess basic technical skills in operating devices and searching for information; however, their ability to evaluate source credibility, understand data security, apply digital ethics, and regulate technology use still requires strengthening. Influencing factors include school facilities, teachers’ competence in technology integration, parental support, and students’ critical thinking skills. The study concludes that strengthening digital literacy requires structured pedagogical strategies and collaboration between schools and families to enable students to use technology critically and responsibly.